2019
DOI: 10.1371/journal.pone.0219317
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induced premature senescence and inhibited epithelial-mesenchymal transition of cancer cells via induction of tumor suppressor Rad9

Abstract: Resveratrol (RSV) has been reported to influence many biological processes, including the stimulation of cellular senescence and inhibition of epithelial-mesenchymal transition (EMT). In this research, we explored the mechanisms of RSV on EMT and cellular senescence through the expression of a DNA damage response (DDR) protein, Rad9, in breast and lung cancer cell lines. Upon treating breast and lung cancer cell lines with RSV at the concentrations of 10–50 μM, Rad9 expression was increased at both transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…In many tumors, they are lost or inactivated due to mutation(s), making proteins less effective at controlling cell growth and/or repair. In lung cancer, several tumor suppressor function as biomarkers for metastasis and prognosis, such as Rb, P53, PTEN 33, KAI1/CD82 34, PARK2 35 and Rad9 36. A number of studies have also identified aberrant microRNA expression in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In many tumors, they are lost or inactivated due to mutation(s), making proteins less effective at controlling cell growth and/or repair. In lung cancer, several tumor suppressor function as biomarkers for metastasis and prognosis, such as Rb, P53, PTEN 33, KAI1/CD82 34, PARK2 35 and Rad9 36. A number of studies have also identified aberrant microRNA expression in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…By down-regulation of the snail signaling pathway, resveratrol reduces EMT to inhibit the invasion of colon cancer cells [63]. It is worth mentioning that resveratrol activates tumor suppressor Rad9 to induce premature senescence in lung and breast cancer cells [64]. Another published article also demonstrates the capability of resveratrol in the regulation of epigenetic factors [65].…”
Section: Resveratrol In the Treatment Of Cancermentioning
confidence: 97%
“…Thus, cells with a mesenchymal phenotype characterized by a lower proliferation index are less sensitive to the cytotoxic effect of chemotherapy compared to those with an epithelial phenotype [ 75 , 106 , 192 , 193 ]. In addition, several recent studies have demonstrated the direct effect of EMT on the well-known mechanisms of tumor cell tolerance to massive DNA damage associated with DNA repair [ 194 , 195 , 196 ], cell-cycle control [ 197 , 198 , 199 ], inactivation of reactive oxygen species [ 200 , 201 ], and autophagy [ 202 ]. Thus, the molecular mechanisms behind the development of resistance to chemotherapy are diverse and, for many types of cancer, mediated by the launch of EMT; however, their relationship remains poorly understood.…”
Section: Emt and Resistance To Antitumor Therapy: Role In The Formatimentioning
confidence: 99%